Measuring users’ psychological self-withdrawal on mobile social media: the development of a context dependent instrument - Chen, Cheng; Yu, Hong (Frontiers in Psychology, 2024)
Existing measures of self-withdrawal on mobile social media (MSM) do not capture the psychological dimension of withdrawal according to behavior-formation processes. MSM users have many concerns when disclosing information, such as role conflicts and privacy risks, which can result in nondisclosure. We call these negative feelings associated with MSM use "psychological self-withdrawal" (PSW) and develop a latent variable to measure it. Using a mixed-methods design, this study develops and validates an instrument for measuring PSW in the WeChat context, based on focus-group interviews (seven participants), one-on-one interviews (eight participants), and a survey of 1200 WeChat users. Our PSW measure is a four-item instrument designed to measure PSW in the WeChat context. The results of two exploratory factor analysis pilot tests (n = 91 and n = 81) and a final confirmatory factor analysis test (n = 1200) indicate that the PSW measure has good internal consistency (α = 0.839), factorial validity, and a single-factor structure.